ESTIMASI SIMPANAN KARBON PADA BIOMASSA MANGROVE DI TAHURA NGURAH RAI - Ni Luh Putu Ratih Pravitha; I Wayan Gede Astawa Karang; Made Suartana (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2022)
Mangroves contribute to mitigating climate change by storing carbon. As mangrove forests have a high rate of carbon sequestration and storage, carbon stock calculations are required to quantify the accumulation of carbon stored in a site to determine its involvement in decreasing greenhouse gas emissions. This study aims to estimate carbon storage at the Mangrove Information Center (MIC) by using an allometric calculation of the mangrove above-ground biomass data. Data collection was carried out on January 10-14, 2022 at the MIC, with an area of 322 ha. The method used is a 1000 meters line transect plot divided into 15 measuring plots in three mangrove ecological zones (front, middle, and back). Biomass data were taken in a non-destructive way based on measurements of the circumference girth at breast height (GBH) and the results were calculated using allometric. According to data analysis, the average total surface biomass of mangroves in MIC is 781.30 kg, with estimated carbon storage in MIC is 36,727 tons/ha. Overall, the total carbon stock in the stratum MIC is 11.826,253 tons. The highest estimated carbon storage is in Plot 9, which is 91,799 tons/ha, while the lowest estimated carbon storage is in Plot 2, which is 13,873 tons/ha. The high numbers of carbon storage from mangrove above-ground biomass are mostly found in the middle and front zones because of the very dense mangrove density. Keywords: mangrove; above-ground carbon estimation; climate change mitigation